2022
DOI: 10.1186/s12893-022-01683-z
|View full text |Cite
|
Sign up to set email alerts
|

Prepectoral breast reconstruction with complete anterior implant coverage using a single, large, square-shaped acellular dermal matrix

Abstract: Background Several studies have discussed various methods of prepectoral direct-to-implant (DTI) breast reconstruction using an acellular dermal matrix (ADM) prosthesis to achieve full coverage. However, methods for anterior coverage have rarely been reported. In this study, prepectoral DTI breast reconstruction with complete anterior implant coverage was performed using a square piece of ADM. This study aimed to introduce our prepectoral DTI technique and determine its functional and cosmetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Eighteen studies reported postoperative infection rates 3,4,11–26 . Overall, the rate of surgical site infections was 2.6% (n = 35/1369) and 4.1% (n = 73/1767) after prepectoral and subpectoral implants, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eighteen studies reported postoperative infection rates 3,4,11–26 . Overall, the rate of surgical site infections was 2.6% (n = 35/1369) and 4.1% (n = 73/1767) after prepectoral and subpectoral implants, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it is worth noting that the definition of surgical revision varies in each study. While most studies only considered unexpected or salvage reoperation as reintervention (Mirhaidari et al, 21 Hong et al 15 ), some studies included fat grafting as reintervention (Manrique et al, 3 Bernini et al 12 ) and others included revision for aesthetic concerns as reintervention (Antony et al, 11 Nealon et al 23 ). While some might argue that fat grafting should not be considered a complication, we believe that fat grafting should be counted as a reintervention as every additional procedure after index procedure confers risk for patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations